The Constitution of Pakistan Issues: Challenges and Options - Alaa M. Bokhari (Journal of Political Studies, 2007)
On August 14th, 1947, Pakistan was carved out on the map of the world for the Muslims of India in order so that they could live in peace and harmony, according to the principles of Islam, free to pursue all spiritual and worldly endeavours in a homeland of their own. Though full of hope and nationalistic fervour; the people of Pakistan were unable to fully realize the dream of their own personalized utopian state because of a variety of devastating crises plaguing the newly born state. From the pro9blems of the refugees to the crippling water and food shortage to the failing healthy of the father of the nation and a serious lack of capable political leaders at the helm of the state, the resultant ominous delay in constitution-making caused serious issues that were to plague Pakistan for the year to come. The lack of consensus between the two wings of the state in all matters ranging from the relationship between Islam and the state to the issue of selecting the national language causes Pakistan to be without a constitution for nearly nine years and in a state of perpetual political chaos and instability. Two constitutions and numerous heads of state later, in 1973 a constitution was formulated that had been the product of a democratically elected legislature. However, it failed to create a balance of power between the various branches of government and especially the balance between the powers of the army and the government. Numerous such issues and the challenges faced by the constitution today are discussed in the following pages and several thought provoking options have also been suggested with particular emphasis of strengthening the legislature and making the parliament the true sovereign body it needs to be.